Mutu organoleptik wadi ikan Patin (Pangasius sp) selama penyimpanan di dalam air - R Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
This study aims to determine the durability of Catfish wadi that is stored in a plastic bucket filled with water maximally, so that the results of this study can be adopted by the public to store processed products of fish wadi with low salt content. The results of the study up to the storage period of Catfish wadi based on the organoleptic test results by 5 trained panelists on the 30th day showed that the Catfish wadi product was still favored by the panelists. The average value of each test criterion: Appearance (value 6.6) criteria: clean, attractive and there is no mucus or mold yet; Aroma (value 6.0), wadi's distinctive aroma is quite sharp; Texture (value 6.0), the criteria are quite compact; Wadi taste after fried (value 6.2), the criteria are quite good. Keywords : Wadi of Catfish, organoleptic quality, durability.